2008
DOI: 10.1063/1.3021462
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of Ge1Sb2Te4 face centered cubic phase

Abstract: The aim of this article is to study the properties of the crystalline face centered cubic Ge 1 Sb 2 Te 4 phase as a function of annealing and measuring temperature. This material is one of the stoichiometric members of the Ge:Sb:Te family, which is widely used in the phase change data storage and one candidate for multistate recording. The electrical properties of this material have been investigated using two independent methods, the four probe impedance and the Hall measurements, and the results are interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…As Zhang et al, [ 4 ] Prokhorov et al, [ 5 ] Siegrist et al, [ 6 ] and Volker et al [ 8 ] have already done the former and elucidated the impact of annealing temperature on step-annealed fi lms of Ge 1 Sb 2 Te 4 , elaborating the stoichiometry aspect seems most rewarding. For this reason, the data that will be discussed in the following were obtained from initially as-deposited amorphous fi lms, which were annealed (and crystallized) at 275 °C (GeTe) and 250 °C (all other compositions) prior to the measurements, i.e., we varied the stoichiometry x , but kept the annealing temperature constant (275/250 °C).…”
Section: Crystallization and Annealing Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…As Zhang et al, [ 4 ] Prokhorov et al, [ 5 ] Siegrist et al, [ 6 ] and Volker et al [ 8 ] have already done the former and elucidated the impact of annealing temperature on step-annealed fi lms of Ge 1 Sb 2 Te 4 , elaborating the stoichiometry aspect seems most rewarding. For this reason, the data that will be discussed in the following were obtained from initially as-deposited amorphous fi lms, which were annealed (and crystallized) at 275 °C (GeTe) and 250 °C (all other compositions) prior to the measurements, i.e., we varied the stoichiometry x , but kept the annealing temperature constant (275/250 °C).…”
Section: Crystallization and Annealing Effectmentioning
confidence: 99%
“…Following the experimental procedures already applied and outlined in a previous study, [ 6 ] we characterized the electrical, optical, and structural properties of the fi lms by sheet resistance, Hall effect, Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). However, in contrast to preceding investigations, [4][5][6][7] where the annealing temperature T a was varied at constant stoichiometry x (Siegrist et al: [ 6 ] T a = 150 ... 325 °C, x = 1/2), we varied the stoichiometry rather than the annealing temperature ( T a = 250/275 °C, x = 3/4 ... 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3(c). It has been confirmed that the carrier concentration of GST-124 is much higher than that of GST-225 in both amorphous and polycrystalline state, and the mobility and the thermal conductivity of the two materials are not very different [13,14]. The conductivity of the materials can be given by the equation (1) as follows:…”
Section: Resultsmentioning
confidence: 95%
“…18 cm -3 [32] to ≈10 22 cm -3 [29]. Also, the large dielectric constant of GeSb x Te y [28] further reduces the energy-cost associated with carrier-concentrations gradients.…”
Section: Figmentioning
confidence: 99%